Factors Associated With Waiting Time for Breast Cancer Treatment in a Teaching Hospital in Ghana. - Dedey, F.; Wu, L.; Ayettey, A.H.; Sanuade, O.A.; Akingbola, T.S.; Hewlett, S.A.; Tayo, B.O.; Cole, H.; de-Graft Aikins, A.; Ogedegbe, G.; Adanu, R. (My University, 2016)
Background. Breast cancer is the leading cause of cancer-related mortality among women in Ghana. Data are limited on the predictors of poor outcomes in breast cancer patients in low-income countries; however, prolonged waiting time has been implicated. Among breast cancer patients who received treatment at Korle Bu Teaching Hospital, this study evaluated duration and factors that influenced waiting time from first presentation to start of definitive treatment. Method. We conducted a hospital-based retrospective study of 205 breast cancer patients starting definitive treatment at Korle Bu Teaching Hospital between May and December 2013. We used descriptive statistics to summarize patient characteristics. Mann–Whitney U and Kruskal–Wallis tests and Spearman rank correlation were performed to examine the patients, health system, and health worker factors associated with median waiting time. Poisson regression was used to examine the determinants of waiting time. Results. The mean age of the patients was 51.1 ± 11.8 years. The median waiting time was 5 weeks. The determinants of waiting time were level of education, age, income, marital status, ethnicity, disease stage, health insurance status, study sites, time interval between when biopsy was requested and when results were received and receipt of adequate information from health workers. Conclusion. A prolonged waiting time to treatment occurs for breast cancer patients in Ghana, particularly for older patients, those with minimal or no education, with lower income, single patients, those with late disease, those who are insured, and who did not receive adequate information from the health workers. Time to obtain biopsy reports should be shortened. Patients and providers need education on timely treatment to improve prognosis.
Keywords: breast cancer; Ghana; health system factors; patient factors; waiting time